Expression and Signaling of Group I Metabotropic Glutamate Receptors in Astrocytes and Microglia - Knut Biber; David Laurie; Achim Berthele; Bernd Sommer; Thomas R. Tölle; Peter‐J. Gebicke‐Härter; Dietrich van Calker; Hendrikus Boddeke (1999)
Abstract: Stimulation of astrocytes with the excitatory neurotransmitter glutamate leads to the formation of inositol 1,4,5‐trisphosphate and the subsequent increase of intracellular calcium content. Astrocytes express both ionotropic receptors and metabotropic glutamate (mGlu) receptors, of which mGlu 5 receptors are probably involved in glutamate‐induced calcium signaling. The mGlu 5 receptor occurs as two splice variants, mGlu 5a and mGlu 5b , but it was hitherto unknown which splice variant is responsible for the glutamate‐induced effects in astrocytes. We report here that both mRNAs encoding mGlu 5 receptor splice variants are expressed by cultured astrocytes. The expression of mGlu 5a receptor mRNA is much stronger than that of mGlu 5b receptor mRNA in these cells. In situ hybridization experiments reveal neuronal expression of mGlu 5b receptor mRNA in adult rat forebrain but a strong neuronal expression of mGlu 5a mRNA only in olfactory bulb. Signals for mGlu 5a receptor mRNA in the rest of the brain were diffuse and weak but consistently above background. Activation of mGlu 5 receptors in astrocytes yields increases in inositol phosphate production and transient calcium responses. It is surprising that the rank order of agonist potency [quisqualate > (2 S , 1′ S ,2′ S )‐2‐(carboxycyclopropyl)glycine = trans ‐(1 S ,3 R )‐1‐amino‐1,3‐cyclopentanedicarboxylic acid (1 S , 3 R ‐ACPD) > glutamate] differs from that reported for recombinantly expressed mGlu 5a receptors. The expression of mGlu 5a receptor mRNA and the occurrence of 1 S , 3 R ‐ACPD‐induced calcium signaling were found also in cultured microglia, indicating for the first time expression of mGlu 5a receptors in these macrophage‐like cells.